2021
DOI: 10.3389/fnut.2021.714567
|View full text |Cite
|
Sign up to set email alerts
|

Regulative Mechanism of Guanidinoacetic Acid on Skeletal Muscle Development and Its Application Prospects in Animal Husbandry: A Review

Abstract: Guanidinoacetic acid is the direct precursor of creatine and its phosphorylated derivative phosphocreatine in the body. It is a safe nutritional supplement that can be used to promote muscle growth and development. Improving the growth performance of livestock and poultry and meat quality is the eternal goal of the animal husbandry, and it is also the common demand of today's society and consumers. A large number of experimental studies have shown that guanidinoacetic acid could improve the growth performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 101 publications
(105 reference statements)
0
22
0
Order By: Relevance
“…Therefore, supplementation of creatine slows down endogenous creatine synthesis. Recently, it has been suggested that the bacterial flora in a healthy gut may accelerate the synthesis of GAA by secreting the enzyme guanidinoacetase, interlinking the synthesis of GAA and the microorganisms of the gastrointestinal tract 17,45,48 …”
Section: Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, supplementation of creatine slows down endogenous creatine synthesis. Recently, it has been suggested that the bacterial flora in a healthy gut may accelerate the synthesis of GAA by secreting the enzyme guanidinoacetase, interlinking the synthesis of GAA and the microorganisms of the gastrointestinal tract 17,45,48 …”
Section: Biosynthesismentioning
confidence: 99%
“…The basic unit of muscle is the myofiber which is derived from stem cell myoblasts. Normally, protein biosynthesis and degradation rates of myofibers are in a relatively balanced state 17,18 . When protein synthesis is higher than degradation, muscle mass increases 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the wide application of GAA in food, feed and medicine, a green, environmentally friendly and safe method of GAA production is needed [5]. At present, the synthesis of GAA in industry is based on the chemical synthesis method.…”
Section: Introductionmentioning
confidence: 99%
“…Guanidine acetic acid (GAA) is the precursor of creatine, which is synthesized by arginine and glycine in the kidney, liver, and pancreas; methylated to creatine and then involved in energy and protein metabolism ( 3 ). In vitro experiments have shown that GAA could promote the rate of fusion of myotubes in C2C12 myoblasts and increase the thickness of myotubes and cross-sectional area of the gastrocnemius muscle ( 4 ).…”
Section: Introductionmentioning
confidence: 99%